Accidentally Case of Chilaiditi’s Syndrome in COVID-19 Geriatric Patient - Yoga, Vesri; Abdullah, Murdani; Arnelis, Arnelis (The Indonesian Society for Digestive Endoscopy, 2022)
Chilaiditi’s syndrome is a rare disease with an incidence of 0.025-0.28% cases, where it shows colon interposition between diaphragm and right lobe of liver. Usually related to congenital malformation include the absence, weakness, or elongation of suspensory ligaments of transversal colon or falciform ligaments. The 83-year-old woman was admitted with 1-week history of fatigue, lacked the will to eat and drink. Nausea and vomiting were sometimes accompanied with abdominal pain. Patient often had difficulty in defecating even though she had been eating fruits, she often needed laxatives. Patient had a history of osteoarthritis and hypertension.Physical examination appeared moderately-ill, with gasglow coma scale (GCS) 14 and blood pressure 150/90 mmHg. From abdomen epigastric tenderness (+). From thoracic X-ray found visible interposition of colon at right-upper quadrant of abdomen. Geriatric index fall risk assessment = 11 and mini mental state examination (MMSE) = 22. This patient was a geriatric patient with multiple diagnosis and frailty. Patient had a history of osteoarthritis contributes to patient’s instability. Chronic constipation was also quite disturbing cause an interposition of colon. Patient had coincidence with COVID-19 with comorbidity and geriatric syndrome. Thorough care, close monitoring, and optimal management should be applied.